Technology Parks in Malaysia: An Exploratory Study on the Role of Government, Other Success Factors, and the Benefits to the Country - Gopinathan, Sisupal Manu (2003)
Technology and science parks have existed in Malaysia since the late Eighties. However, it has been only in the last few years that there has been a re-emergence of interest in this area. There are a number of technology parks in Malaysia. These include the Multimedia Super Corridor (MSC), Technology Park Malaysia (TPM) in Bukit Jalil, and Kulim High Technology Park (KHTP) in Kulim, Kedah. This paper intends to provide a critical view on the role of government in the implementation and success of technology parks. The paper would also look into the other factors that contribute to the successful creation of these developments. In order to identify these factors that contribute to its success, the paper would also draw a comparison between the technology parks in Malaysia and those outside the country, such as Silicon Valley and other such technopoles. The paper also intends to look into the benefits created by these developments. These would also be compared with the benefits gained from technology parks around the world. Keywords: Technology parks, Malaysia, science parks, technopoles